THE NEW ILLUSTRATED ENCYCLOPEDIA OF AIRCRAFT - Mondey, David; Taylor, Michael Taylor (Greenwich Editions, 2000)
A complete guide to aircraft from their beginnings to the present day. Includes both Military and Civil aircraft in one comprehensive volume. Illustrated with over 1000 photographs.